How to do theory di Wolfgang Iser (ENTHYMEMA, 2011)
Review of Wolfgang Iser’s How to Do Theory, Malden, MA/Oxford: Blackwell 2006, a volume conceived as a sort of guide to the most important literary theories of the Twentieth century, in which the German scholar presents his own idea of literature as well as the importance of a shift towards an anthropology of literature.